Cheetah [videorecording (DVD)] - Coogan, Keith, 1970-; Deakins, Lucy, 1971-; Mothupi, Collin; Caillou, Alan, 1914-2006 (Buena Vista Home Entertainment, 2002)
Two California teenagers find their vacation in Africa turned into an incredible adventure and a struggle for survival.